Konsekuensi Lingkungan Dan Sosial Dari Penebangan Liar: Implikasi Hukum Dan Strategi Penegakan - Lestari, Nopita; Rahmatiar, Yuniar; Abas, Muhamad (PAMALI: Pattimura Magister Law Review, 2024)
Introduction: Illegal logging is a critical issue that harms the environment, economy, and society. This activity results in forest degradation, increases the risk of natural disasters, and undermines the economic potential of sustainable natural resource management.Purposes of the Research: This study aims to analyze the environmental impacts of illegal logging and the penalties imposed on offenders under applicable laws.Methods of the Research: The study employs a normative juridical method, focusing on the legal framework surrounding illegal logging. The analysis highlights the environmental and economic consequences of illegal logging and evaluates the effectiveness of law enforcement measures.Results of the Research: Illegal logging leads to environmental degradation, including heightened risks of flooding and landslides due to soil instability and reduced water absorption. Economically, it diminishes potential revenue from sustainably managed natural resources. Offenders may face sanctions such as fines, compensation, and rehabilitation costs. Strong law enforcement and collaboration between the government, NGOs, communities, and the private sector are essential for effective forest protection.